A Reply to Comment on Kluckow M. Barriers to the Implementation of Newborn Pulse Oximetry Screening: A Different Perspective. Int. J. Neonatal Screen. 2018, 4(1), 4 - Martin Kluckow (MDPI AG, 2018)
The commentary provided by Gentles et al. argues for the implementation of a universal pulse oximetry screening program, and I agree that, if it is possible, this is the optimum way to introduce this important health care measure for all of the reasons set out by the authors.[...]